Influence of cytochrome P450 genotype on the plasma disposition of prochlorperazine metabolites and their relationships with clinical responses in cancer patients. (May 2018) - Tashiro, Masaki; Naito, Takafumi; Kagawa, Yoshiyuki; Kawakami, Junichi
Background: Oral prochlorperazine, a dopamine D2 receptor antagonist, is largely metabolized to sulphoxide, 7-hydroxylate and N -desmethylate by cytochrome P450s (CYPs). This study evaluated the influence of CYP genotype on the plasma dispositions of prochlorperazine and its metabolites and their relationships with antiemetic efficacy and prolactin elevation in cancer patients. Methods: Forty-eight cancer patients treated with oral prochlorperazine were enrolled. Plasma prochlorperazine and its metabolites concentrations and serum prolactin concentration were determined at 12 h after the evening dosing. The genotypes of CYP2C19, CYP2D6 and CYP3A5 and the incidences of nausea and vomiting were investigated. Results: The plasma concentrations of the prochlorperazine metabolites were weakly correlated with that of the parent drug. The CYP genotypes did not affect the plasma concentrations of prochlorperazine and its metabolites. The plasma concentrations of prochlorperazine and its metabolites were not associated with the incidences of nausea and vomiting. The incidence of vomiting was significantly higher in females than in males. The serum prolactin concentration was weakly correlated with the plasma concentrations of prochlorperazine and its metabolites. The plasma concentrations of prochlorperazine metabolites rather than the parent drug had a weaker relation to serum prolactin concentration. Conclusions: The CYP genotypes did not affect the plasma dispositions of prochlorperazine and its metabolites. The prochlorperazine metabolites did not have a strong effect on antiemetic efficacy, while they were slightly associated with prolactin secretion in cancer patients.